Virulence of conidia Beauveria bassiana (Bals.) as a bioinsecticide against Crocidolomia pavonana (F.) (Lepidoptera: Pyralidae) on broccoli plants - MUHAMMAD SAYUTHI; ALFIAN RUSYDI; HASNAH HASNAH; NAILA EVI AZAHRA (Universitas Syiah Kuala, 2022)
Crocidolomia pavonana is an important pest of broccoli plants. Pest control is currently still using chemical pesticides that negatively impact the environment. It is hoped that Beauveria bassiana will become one of the environmentally friendly bioinsecticides. The research aimed to study the virulence level of conidia density of B. bassiana as a bioinsecticide against C. pavonana pests on broccoli plants. This experiment used a completely randomized design consisting of 5 treatments and four replications so that 20 experimental units were obtained. The Basic Plant Protection Laboratory and Plant Pest Science Laboratory Faculty of Agriculture, Syiah Kuala University as the research location, which was carried out from January to September 2021. The parameters observed were larval mortality, pupae formed, imago appeared, an incubation period of B. bassiana conidia, and average time of C. pavonana. The results showed that B. bassiana with conidia density of 108/mL distilled water was effective as a bioinsecticide against C. pavonana. The highest percentage of C. pavonana mortality observed at 6 Days After Application (DAA) occurred at a density of 108 conidia/mL of water (97.50%), and the lowest was at a density of 102 conidia/mL of distilled water (62.50%). The percentage of pupae formed was observed. At 7, DAA was 15% using a density of 102 conidia /mL aquadest. Produce 5%, a density of 104 conidia/mL of distilled water was used. The percentage of imago that appeared with a conidia density of 102/mL of distilled water killed at 14 DAA yielded 15%, and 5% resulted from a density of 104 conidia/mL of distilled water. The fastest incubation occurred at a density of 108 conidia/mL of distilled water with a time of 3.50 days. Death of C. pavonana at 3.03 days required conidia density of B. bassiana 102/mL of distilled water.